10-year practice-based evaluation of ceramic and direct composite veneers. Issue 5 (May 2022) - Mazzetti, Thais; Collares, Kauê; Rodolfo, Bruna; da Rosa Rodolpho, Paullo Antônio; van de Sande, Françoise Hélène; Cenci, Maximiliano Sérgio
Abstract: Objectives: This 10-year practice-based study aimed to compare survival and success of direct resin composite and ceramic veneers placed in a private dental practice, between January 2008 and March 2014. Methods: Data were retrieved from a clinical practice's records and were anonymized typed into electronic files. All veneer information was recorded, including previous restorations, repairs or failures, materials used, dates, patient, and age. Results: We analyzed 1459 veneer restorations, of which 1043 (71.5%) were direct composite, and 416 (28.5%) were ceramic, placed in 341 patients. The mean patients' age was 47.8 years, and the mean number of restorations per patient was 4.3 restorations. During all follow-up, 957 (65.6%) veneers were successful without any repair, 252 (17.3%) were repaired and still in place, and 250 (17.1%) had a failure that resulted in replacement. Replacements were usually carried out with the same material placed at first. Considering success analysis, annual failure rates (AFR) for veneers in 5 and 10 years were 9.1% and 10% for direct composite and 2.9% and 2.8% for ceramic, respectively. Survival analysis showed AFR of 3.9% and 4.1% for composite and 1.4% and 1.2% for ceramic at the same periods. Cox regression was made for both success and survival outcomes. Composite veneers presented a higher risk of failure than ceramic veneers with higher hazard ratios for survival (HR) [HR 4.00 (2.74–5.83)] and success [HR 5.16 (2.65–10.04)]. Significance: Ceramic veneers had superior longevity than direct composite veneers in both success and survival analysis. Highlights: Ceramic veneers show overall higher longevity than composite veneers. Composite veneers are a more conservative alternative and shows acceptable longevity. While composite veneers demanded more reinterventions, can be considered long-lasting.